Mutation of rpoB Shifts the Nutrient Threshold Triggering Myxococcus Multicellular Development - Eisner, Sabrina A.; Velicer, Gregory J.; Yu, Yuen-Tsu N. (Frontiers in Microbiology, 2022)
The ability to perceive and respond to environmental change is essential to all organisms. In response to nutrient depletion, cells of the soil-dwelling δ-proteobacterium Myxococcus xanthus undergo collective morphogenesis into multicellular fruiting bodies and transform into stress-resistant spores. This process is strictly regulated by gene networks that incorporate both inter- and intracellular signals. While commonly studied M. xanthus reference strains and some natural isolates undergo development only in nutrient-poor conditions, some lab mutants and other natural isolates commit to development at much higher nutrient levels, but mechanisms enabling such rich-medium development remain elusive. Here we investigate the genetic basis of rich-medium development in one mutant and find that a single amino-acid change (S534L) in RpoB, the β-subunit of RNA polymerase, is responsible for the phenotype. Ectopic expression of the mutant rpoB allele was sufficient to induce nutrient-rich development. These results suggest that the universal bacterial transcription machinery bearing the altered β-subunit can relax regulation of developmental genes that are normally strictly controlled by the bacterial stringent response. Moreover, the mutation also pleiotropically mediates a tradeoff in fitness during vegetative growth between high vs low nutrient conditions and generates resistance to exploitation by a developmental cheater. Our findings reveal a previously unknown connection between the universal transcription machinery and one of the most behaviorally complex responses to environmental stress found among bacteria.